Peningkatan Hasil Belajar Pembagian Melalui Problem Based Learning Berbantuan Media Simbata Kelas 3 Sdn Sawah Besar 01 - Destari, Arum; Azizah, Mira; Lestari, Alberta Budi (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
This study aims to determine the learning outcomes of the division of elementary school students through the Problem Based Learning model assisted by simbata learning media (mathematical division machine). The subjects of the study amounted to 28 students consisting of 13 boys and 15 girls. This research is a class action research that refers to the Kemmis and Taggart model. The study was conducted in 2 cycles consisting of stages of planning, action and observation, reflection. Research data in the form of cognitive learning results taken with description test techniques. Meanwhile, psychomotor learning outcomes are taken using psychomotor assessment sheets through observer observation. Cognitive learning outcomes were 57.5% in the pre-cycle, 74.29% in cycle I, and 8 5.89% in cycle II. This shows an increase in the use of Simbata learning media in the material for the division of grade 3 elementary school Problem Based Learning model.